Kajian Hak Asasi Manusia Dalam Perlindungan Hukum Terhadap Korban Kekerasan Dalam Rumah Tangga - Riupassa, Hendrina; Maramba, Rambu Susanti Mila; Indah, Rambu Hada (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The wellbeing of its citizens must be prioritized if a strong nation is to be realized. especially with regard to establishing a calm and harmonious household. Laws and regulations also make this right evident. Nonetheless, there are still unsolved problems in society, such as the existence of women who are victims of domestic abuse. Therefore, it is decided that a research from the standpoint of human rights is required. Because the research object is domestic violence, normative research is used in this study. From a human rights viewpoint, the primary subject of discussion is the legal protections available to women who are victims of domestic abuse. The study employed many research methodologies, including the statute.